2011
DOI: 10.1620/tjem.225.195
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Method to Detect Microalbuminuria by Measuring the Total Urinary Protein-to-Creatinine Ratio in Diabetic Patients

Abstract: Diabetes and chronic kidney disease (CKD) which are risk facters of cardiovascular disease, are increasing global public health problems. Microalbuminuria is an early sign of progressive cardiovascular and renal disease in individuals with or without diabetes. Screening for microalbuminuria and early treatment are recommended for patients with increased cardiovascular and renal risk factors. However, the procedure used to measure urinary albumin is expensive. Alternatively, the measurement of total urinary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…However, other studies have examined the relationship between the ACR and PCR (Atkins et al 2003;Methven et al 2010;Smith et al 2012). Our group previously reported that the PCR is highly correlated with the ACR and that an ACR of 30 mg/g creatinine is equivalent to a PCR of approximately 0.08-0.09 g/g creatinine, based on the analyzed datasets (Yamamoto et al 2011(Yamamoto et al , 2014. Fisher et al (2013) reported that the ACR and PCR are relatively similar and that an ACR of 30 mg/g creatinine is equivalent to a PCR of approximately 0.08-0.11 g/g creatinine based on regression and Lowess smooth analyses in a recent large CKD cohort study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, other studies have examined the relationship between the ACR and PCR (Atkins et al 2003;Methven et al 2010;Smith et al 2012). Our group previously reported that the PCR is highly correlated with the ACR and that an ACR of 30 mg/g creatinine is equivalent to a PCR of approximately 0.08-0.09 g/g creatinine, based on the analyzed datasets (Yamamoto et al 2011(Yamamoto et al , 2014. Fisher et al (2013) reported that the ACR and PCR are relatively similar and that an ACR of 30 mg/g creatinine is equivalent to a PCR of approximately 0.08-0.11 g/g creatinine based on regression and Lowess smooth analyses in a recent large CKD cohort study.…”
Section: Discussionmentioning
confidence: 94%
“…This study was based on a secondary analysis of our two previous outpatient studies, with 150 diabetic patients included in the first study (2011) (hereafter, Study 1) (Yamamoto et al 2011) and 784 cardiovascular patients included in the second study (2014) (hereafter, Study 2) (Yamamoto et al 2014). The methods and primary results were reported in detail in each article.…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The optimal cut-off value for predicting microalbuminuria for TPCR was found to be 119 mg/g creatinine. Various studies have reported positive correlation between TPCR and ACR [13][14][15]. For the first time, the study of Yamamoto et al [15] has shown that TPCR measurement in diabetic patients predisposes to the presence of microalbuminuria.…”
Section: Discussionmentioning
confidence: 98%
“…The association between proteinuria and albuminuria has been shown in many studies [11][12][13][14][15]. The cutoff value that predicts the micro-albuminuria of TPCR has been determined only in a limited number of studies [14,15].…”
Section: Introductionmentioning
confidence: 99%